Evaluasi Kesesuaian Lahan Untuk Tanaman Durian Menggunakan Metode Matching - Muhammad Frido Saputra; Sidharta Adyatma; Deasy Arisanty (Universitas Negeri Gorontalo, 2021)
Land suitability evaluation is a process of assessing the potential of land for a particular use, whether in agriculture, plantation, tourism, land conservation, or other types of use. This study aims to determine the land suitability class for durian plants in Aranio District and determine the inhibiting factors on the land using the matching method. The population in this study was 12 land units and each unit was taken 2 samples. Land units are obtained from overlay maps of landforms, slope maps, geological maps, soil association maps, and land use maps. The results showed that the land in Aranio District was included in the suitability class S2 (moderately suitable) with an area of 15069.68 hectares or 33.13%, S3 (marginally suitable) with an area of 1485.78 hectares or 3.27%, and N1 (not current suitable) with an area of 3980.03 hectares or 8.75%. The limiting factor is slope, erosion hazard, pH, soil depth, surface rock, alkaline saturation, flood hazard, phosphate, K2O, and N-Total. The villages in the Aranio sub-district are used to develop durian plants because they have land suitability classes of S2 and the use of shrubs, fields, and mixed gardens are above 50%, namely Tiwingan Baru and Tiwingan Lama villages.